Representation of Mental Health Disorders in Postpartum Women in the Film "Baby Blues" - Mayang, Citra Sekar; Aziz, Zuhdan (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Purpose: The purpose of this research is to explain about how the representation of mental health disorders in postpartum women in the film "Baby Blues". Methodology: This research uses a qualitative approach and film analysis using the Roland Barthes semiotic method, with data collection techniques through documentation and literature study. Results: The results of this study by looking at denotation, connotation, and myth, then depicted in the film Baby Blues represent many women experiencing mental health disorders after childbirth. Furthermore, the results of the myth, this film presents many traditional views, namely gender stereotypes in society that can increase the risk of mental health disorders in postpartum women. This research is expected to make an important contribution to film studies, especially the influence of visual. Representation in films on people's perceptions and views related to mental health issues experienced by postpartum women through symbols, signs, and visual language to describe and communicate this issue. Applications/Originality/Value: This research seeks to make a film narrative more interesting in describing an issue so that it can be a guideline for filmmakers to produce more detailed and more accurate representations of mental health-related issues in future works.